Multilingualism and Personality Traits among Malay Primary School Students in Vernacular Schools - Latiff Azmi, Mohd Nazri (2013)
The study investigates a group of Malay students who study Malay, Chinese and English languages at eight vernacular (Chinese) schools in a state of Malaysia. The focus of the study is to examine the process of the students acquire the second and third languages (Mandarin and English) and at the same time they struggle to master their mother tongue or their first language, Malay. Most importantly, the study seeks the dominant personality traits of the students and tries to find the relationships between personality traits and multilingualism. Interviews with the students and teachers and also class observation have helped the researcher to understand the challenges faced by the students. The study reveals some findings which closely related to sociolinguistics aspects which show that the students have to sacrifice their first language in order to master the target languages which are Mandarin and also English. They have a strong belief that although they have sacrificed a lot of time and effort in mastering the target language, they try their best to uphold their personality traits and self-identity.